Desain Formulir Pelaporan Kematian Perinatal Berbasis Elektronik dengan Menggunakan Metode Waterfall - Apriliani, Ima; Syahidin, Yuda; Suryani, Ade Irma (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2024)
Research that has been conducted at the Mother and Child Hospital X Bandung City aims to create an electronic-based perinatal death reporting form design to facilitate medical recorders in managing perinatal death data effectively, efficiently and accurately. The problems faced are the absence of classification of reports based on perinatal, recording and searching for death data still using manual methods which result in mismatches in data, loss of data and delays in making perinatal death reports. In this research, the method used is qualitative research with a descriptive approach, and uses observation, interviews and documentation as data collection techniques. The Waterfall method is used as a development method that utilizes Visual Studio 2010 and Microsoft Access applications to facilitate system design. The method that has been applied produces a perinatal death reporting system that allows to reduce recording time, search for data and facilitate the work of medical recorders to obtain the reporting.